Multi-user Data Sharing Authentication Protocol for Cloud Computing with Seclusion (International Journal of Advanced Research in Science, Management and Technology, 2015)
Cloud computing will be a good emerging details interactive paradigm to be able to understand  user's  info remotely maintained inside a good on the internet cloud server. Cloud  providers give the brilliant  conveniences  for the users to help appreciate your on-demand cloud applications devoid of considering the local infrastructure limitations. during your current  information  accessing,  other  users  may be   in   an  collaborative relationship,  along with   and so  data sharing becomes  significant   for you to  achieve productive benefits.  The latest   security   products  mainly focus  towards  authentication to realize the item the user’s privative  data   are not able to   be  illegally accessed, but neglect  an   highly discreet  privacy issue  throughout   a   end user   challenging  the cloud server  to   get   various other  users  with regard to   data  sharing.  your  challenged  access   get  itself  will probably  reveal  the  user’s privacy  simply no  matter whether  or perhaps  not  This will probably get the  facts   accessibility  permissions.  throughout  the actual  paper, I  propose  the  multi user based privacy-preserving authentication protocol  in order to  address above privacy issue  with regard to  cloud storage. On the  SAPA, 1) shared  gain access to  authority is achieved  by  anonymous  gain access to  request for  matching mechanism  within   safety   as well as  privacy considerations (e.g., authentication, data anonymity,  person  privacy,  as well as  forward security); 2) attribute based  entry  control  is usually  adopted  in order to realize  It   an individual   can   single  access its own  data  fields; 3) proxy re-encryption  can be  applied to help give the data  sharing among  your  multiple users. Meanwhile, universal composability (UC) model is actually standard  in order to  prove  that this  SAPA theoretically  offers   your own  design correctness. It indicates that the proposed protocol  is usually  attractive  regarding  multi-user collaborative cloud applications.
Keywords: Cloud computing, authentication protocol, privacy preservation, multi user, universal composability.